ANALISIS PERAN DIGITAL MARKETING DALAM MENINGKATKAN DAYA SAING DESTINASI WISATA - Ridho Indra Saputra (Yayasan Pendidikan Literasi Borneo, 2025)
This study aims to analyze the role of digital marketing in enhancing the competitiveness of tourism destinations in South Kalimantan, particularly those that are emerging and seeking greater visibility amid regional competition. The advancement of digital technology has transformed tourism promotion, with social media, creative content, and virtual tours becoming key instruments for building destination image and influencing tourist decisions. This research employs a qualitative approach with a case study design through field observations, in-depth interviews with destination managers, local businesses, and tourists, as well as documentation analysis. The findings indicate that digital marketing contributes significantly to increasing visit intention through faster and more effective information dissemination. Strategies such as Instagram marketing, consistent visual content, and the use of digital features strengthen destination image and tourist engagement. However, challenges persist, especially limited human resources and the lack of integrated institutional marketing strategies. This study highlights the importance of improving digital capacity and fostering cross-sector collaboration to strengthen tourism promotion in South Kalimantan.